Tyrosine-Dependent Phenotype Switching Occurs Early in Many Primary Melanoma Cultures Limiting Their Translational Value - Najem, Ahmad; Wouters, Jasper; Krayem, Mohammad; Rambow, Florian; Sabbah, Malak; Sales, François; Awada, Ahmad; Aerts, Stein; Journe, Fabrice; Marine, Jean-Christophe; Ghanem, Ghanem E. (Frontiers in Oncology, 2021)
The use of patient-derived primary cell cultures in cancer preclinical assays, including drug screens and genotoxic studies, has increased in recent years. However, their translational value is constrained by several limitations, including variability that can be caused by the culture conditions. Here, we show that the medium composition commonly used to propagate primary melanoma cultures has limited their representability of their tumor of origin and their cellular plasticity, and modified their sensitivity to therapy. Indeed, we established and compared cultures from different melanoma patients propagated in parallel in low-tyrosine (Ham’s F10) or in high-tyrosine (Ham’s F10 supplemented with tyrosine or RPMI1640 or DMEM) media. Tyrosine is the precursor of melanin biosynthesis, a process particularly active in differentiated melanocytes and melanoma cells. Unexpectedly, we found that the high tyrosine concentrations promoted an early phenotypic drift towards either a mesenchymal-like or senescence-like phenotype, and prevented the establishment of cultures of melanoma cells harboring differentiated features, which we show are frequently present in human clinical biopsies. Moreover, the invasive phenotype emerging in these culture conditions appeared irreversible and, as expected, associated with intrinsic resistance to MAPKi. In sharp contrast, differentiated melanoma cell cultures retained their phenotypes upon propagation in low-tyrosine medium, and importantly their phenotypic plasticity, a key hallmark of melanoma cells. Altogether, our findings underline the importance of culturing melanoma cells in low-tyrosine-containing medium in order to preserve their phenotypic identity of origin and cellular plasticity.